COMPARISON OF DIFFERENT METHODS FOR ESTIMATION OF POTENTIAL EVAPOTRANSPIRATION - Nazeer, M. (The Nucleus, 2010)
Evapotranspiration can be estimated with different available methods. The aim of this research study to compare and evaluate the originally measured potential evapotranspiration from Class A pan with the Hargreaves equation, the Penman equation, the Penman-Montheith equation, and the FAO56 Penman-Monteith equation. The evaporation rate from pan recorded greater than stated methods. For each evapotranspiration method, results were compared against mean monthly potential evapotranspiration (PET) from Pan data according to FAO (ETo=KpanÃ—Epan), from daily measured recorded data of the twenty-five years (1984-2008). On the basis of statistical analysis between the pan data and the FAO56- Penman-Monteith method are not considered to be very significant ( =0.98) at 95% confidence and prediction intervals. All methods required accurate weather data for precise results, for the purpose of this study the past twenty five years data were analyzed and used including maximum and minimum air temperature, relative humidity, wind speed, sunshine duration and rainfall. Based on linear regression analysis results the FAO56 PMM ranked first ( =0.98) followed by Hergreaves method ( =0.96), Penman-Monteith method ( =0.94) and Penman method ( =0.93). Obviously, using FAO56 Penman Monteith method with precise climatic variables for ET 2 R 2 R 2 R 2 R 2 R o estimation is more reliable than the other alternative methods, Hergreaves is more simple and rely only on air temperatures data and can be used alternative of FAO56 Penman-Monteith method if other climatic data are missing or unreliable.